Olive Leaves as a Potential Phytotherapy in the Treatment of COVID-19 Disease; A Mini-Review - Abdelgawad, Shimaa M.; Hassab, Mahmoud A. El; Abourehab, Mohammed A. S.; Elkaeed, Eslam B.; Eldehna, Wagdy M. (Frontiers in Pharmacology, 2022)
Starting from December 2019, COVID-19 pandemic has caused a tremendous economic loss and unprecedented health crisis across the globe. Discovering an effective and safe drug candidate for the treatment of COVID-19 and its associated symptoms became a global urgent demand especially due to limited data that have been released regarding the vaccine efficacy and safety in humans. Reviewing the recent research, Olive leaf was selected as a potential co-therapy supplement for the treatment and improvement of clinical manifestations in COVID-19 patients. Olive leaves were reported to be rich in phenolic compounds such as Oleuropein, Hydroxytyrosol, Verbascoside, Apigenin-7-O-glucoside, Luteolin-7-O-glucoside, and also triterpenoids such as Maslinic, Ursolic and Oleanolic acids that have been reported as anti-SARS-CoV-2 metabolites in recent computational and in vitro studies. Additionally, olive leaf extract was previously reported in several in vivo studies for its anti-inflammatory, analgesic, antipyretic, immunomodulatory and anti-thrombotic activities which is of a great benefit in the control of associated inflammatory cytokine storm and disseminated intravascular coagulation in COVID-19 patients. In conclusion, the described biological activities of olive leaves alongside with its biosafety, availability and low price, make it as a potential candidate drug or supplement to control COVID-19 infection and recommended for clinical investigation